IMPLEMENTASI MULTIMEDIA PEMBELAJARAN BERBASIS ADVENTURE GAME DENGAN MODEL BRAIN BASED LEARNING UNTUK MENINGKATKAN KOGNITIF SISWA PADA MATA PELAJARAN JARINGAN DASAR - Laeliya, Fitri (2017)
This study is motivated by lack of visualization for learning computer network. The purpose of this study is to observe the effect of the use of adventure game based media learning with Brain Based Learning models toward the increased student's cognitive on the subject of computer network and to obtain students' response to multimedia. This study uses experimental research. In accordance with the purpose of this study is to find the specific treatment effect toward another in controlled conditions. In addition, the development of this learning multimedia uses Research and Develompment models. To test the multimedia develop to impelemented is done through expert validation of materials and media, while the students' response to multimedia-based learning adventure game through a questionnaire. From the data processing is done in this study showed: 1) multimedia adventure game shape has beem developed and is considered good and fit to use by the average percentage of eligibility 85.60% by media experts and 93.20% by subject experts. 2) this multimedia also obtains positive response from student which is very well categorized with percentage of 84.70%. 3) the increase of cognitive on students has an index gain of 0.46. Thus, multimedia learning in the form of adventure game with Brain Based Learning model developed is feasible to implemented in the learning process and has an influence towards students cognitive.---- Penelitian ini dilatarbelakangi oleh adanya masalah selama pembelajaran Jaringan Dasar. Tujuan penelitian ini adalah untuk melihat pengaruh dari penggunaan media pembelajaran berbasis adventure game dengan model Brain Based Learning terhadap peningkatan kognitif siswa pada mata pelajaran jaringan dasar serta untuk mendapatkan respon siswa terhadap multimedia. Penelitian ini menggunakan metode penelitian eksperimen. Selain itu pengembangan multimedia pembelajaran ini menggunakan model pengembangan Research and Development (R&D). Untuk menguji multimedia yang dikembangkan agar dapat diimplementasikan dilakukan validasi ahli materi dan media, sedangkan respon siswa respon terhadap multimedia pembelalajaran melalui angket. Dari pengolahan data yang dilakukan pada penelitian ini didapatkan hasil: 1) multimedia berbentuk adventure game telah dikembangkan dan dinilai baik dan layak digunakan dengan rata-rata presentase kelayakan 85.60% oleh ahli media dan 93.20% oleh ahli materi. 2) multimedia ini pun mendapat respon positif dari siswa yang dapat dikategorikan baik dengan persentase sebesar 84.70 %. 3) peningkatan kognitif pada siswa memiliki indeks gain sebesar 0.46. Dengan demikian multimedia pembelajaran berbentuk adventure game dengan model Brain Based Learning yang dikembangkan layak untuk diimplementasikan dalam proses pembelajaran dan memiliki pengaruh terhadap peningkatan kognitif siswa.